THE IMPORTANCE OF MUSIC ART IN REVEALING THE ARTISTIC INTEGRITY OF A FILM - Qobilova Shaxnoza Nasrulla qizi (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes the fact that music is an integral part of art and has its place in the cinema. In this regard, the music composed for the film, while having a special place in the film, helps to reveal the essence, idea and artistic integrity.